New record of Pelecitus sp (Nematoda, Onchocercidae) as a parasite of Athene cunicularia (Strigiformes, Strigidae) in southeastern Brazil - Silva, Tarcsio Macedo [UNESP]; Okamoto, Adriano Sakai [UNESP]; Firmino da Silva, Lidiane Aparecida [UNESP]; Smaniotto, Bruna Domeneghetti [UNESP]; Silva, Reinaldo José da [UNESP]; Andreatti Filho, Raphael Lucio [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
The aim of this study was to report the burrowing owl Athene cunicularia as a new host for the filarid nematode Pelecitus sp. in southeastern Brazil for the first time, as well as reporting the occurrence of this nematode species in the body cavity, near the cervical air sac and lung region. This study contributes towards knowledge of parasitism in Brazilian wild birds and an anatomical region of the host as an infection site for Pelecitus sp.

O objetivo do estudo foi relatar, pela primeira vez, a coruja buraqueira Athene cunicularia como um novo hospedeiro para o nematóide filarídeo Pelecitus sp. do Sudeste do Brasil, bem como a ocorrência desta espécie de nematóides na cavidade corporal, próximos à região dos sacos aéreos cervicais e pulmões. Este estudo contribui para o conhecimento do parasitismo em aves silvestres brasileiras e uma região anatômica do hospedeiro como sítio de infecção para Pelecitussp.
Novo registro de Pelecitus sp. (Nematoda, Onchocercidae) como parasita de Athene cunicularia(Strigiformes, Strigidae) no Sudeste do Brasil
Keywords: Parasitic nematodes; Pelecitus sp.; Birds; Strigiformes; Athene cunicularia; Nematóides parasitas; Pelecitus sp.; Aves; Strigiformes; Athene cunicularia